2008
DOI: 10.2337/dc07-1365
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diabetes and Cardiovascular Disease Print Patient Education Materials for Use With Low–Health Literate Populations

Abstract: OBJECTIVE -Populations with the lowest literacy and health literacy in the U.S. are also among those disproportionately burdened by diabetes and its complications. Yet, suitability of publicly available diabetes and cardiovascular (CVD) patient education materials for these patients is not clear. We evaluated selected American Diabetes Association (ADA) and American Heart Association (AHA) print education materials for accessibility and usability characteristics.RESEARCH DESIGN AND METHODS -English-language, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 9 publications
(5 reference statements)
2
53
0
Order By: Relevance
“…16,20,21 Print materials are commonly used to educate patients regarding self-care recommendations; however, many materials do not follow clear communication guidelines and are written at high reading levels, which may present a learning barrier for patients with limited health literacy. 22 It has been previously suggested that evaluations of health literacy and a patient's reading ability may simply be a measurement of cognitive function, and therefore, it is poor cognitive function that is associated with a higher risk of mortality and not specifically health literacy. 23,24 In a large international cohort of hemodialysis patients, a diagnosis of dementia has been shown to be associated with a 1.8-fold increased risk of death among incident patients and a 1.4-fold increased risk of death among prevalent dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…16,20,21 Print materials are commonly used to educate patients regarding self-care recommendations; however, many materials do not follow clear communication guidelines and are written at high reading levels, which may present a learning barrier for patients with limited health literacy. 22 It has been previously suggested that evaluations of health literacy and a patient's reading ability may simply be a measurement of cognitive function, and therefore, it is poor cognitive function that is associated with a higher risk of mortality and not specifically health literacy. 23,24 In a large international cohort of hemodialysis patients, a diagnosis of dementia has been shown to be associated with a 1.8-fold increased risk of death among incident patients and a 1.4-fold increased risk of death among prevalent dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…8 Three resources for development of low-literacy materials were used [9][10][11] for guidance in reducing literacy demand and increasing behavioral activation characteristics of original materials. 6 Additional resources were used for adapting information to meet accessibility needs due to vision impairment 12 and content needs due to physical impairment resulting from diabetes complications or older age 13 (Table 1). Reading grade level and reading ease scores for the print materials and the orally delivered intervention protocol were determined using the Flesch-Kincaid analysis, obtained via computer calculation in Microsoft Word, 2003.…”
Section: Development Of Low-literacy Education Materials and Modulementioning
confidence: 99%
“…3,4 Yet, methods for adapting materials for low literacy are not clearly understood or widely disseminated, and there remains little empirical research testing the usability of literacy-adapted materials. 5,6 The purposes of this study were to develop a lower-literacy patient diabetes and cardiovascular disease (CVD) education and to pilot test its acceptability and usability in a sample of urban, African-American, type 2 diabetic adults with Below Average and Average literacy.…”
mentioning
confidence: 99%
“…Although patient education is considered to be a key component of T2DM care (Funnell et al, 2010), studies show that many patients who have attended a diabetes education program, especially those with low health literacy, still do not know the basics of their disease or self-management skills (Williams, Baker, Parker, & Nurss, 1998). One reason may be that most diabetes self-management education (DSME) programs introduce too much information, present information in a complex manner, and often do not explicitly link education to patient activation (Hill-Briggs & Smith, 2008); thus, little information may be retained or translated into better self-management behaviors. Interventions that explicitly address the challenge that patients across literacy levels face in comprehending, learning, and acting on diabetes self-management concepts are critical to achieving equity in diabetes care (Institute of Medicine, 2009).…”
mentioning
confidence: 99%